(3HTQi GdhUhd Edi CSQGQ Yde GdCUhds - (3GdeGebGfj GdfLaj, eMeO MSf Hf YHO Gddg, J (B1323(3g`s
(3ChdgG (B:s
(3GdMeO ddg hSdGeg Ydi YHGOg GdPjf GUWai hHYO ajbhd(B...(3GdeGebGfj(B...(3EfG deG aQZfG ef GdcdGe Ydi eHGMK GdCdaGX(B... (3QCjfG GdHMK Yf MGd GdbWY hGdXf(B...s
(3BNQgG (B:s
(3eHJhQI GdBNQ, hBNQ GdehLhO efgG(B: ...(3hC(B/(3G eG PcQg aj eSCdI caGjI GdXf aj CUhd GdOjf (B...s
(3JHUQI GdeDda (B:s
(3hPcQg aj (B((3GdCYdGe(B:(3L(B2(3,U(B197) (3HGSe MSf Hf YHO Gddg Hf eMeO HfaS JaGUjd GdJQLeI(B!s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe(B:(3L(B6(3,U(B93s
(3GdPQjYI(B:(3L(B3(3,U(B67(3,Qbe(B409s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3CUhd Gdabgs